PENILAIAN GEDUNG DENGAN PENDEKATAN PENDAPATAN MENGGUNAKAN SIMULASI MONTE CARLO: Studi Kasus: Gedung Thamrin, Jakarta - , HASRUL NASUTION, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Constraints to provide the estimated value represents the state of the market or uncertain information in long-term investment decisions, can now be facilitated by advances in technology. Estimates with a value, often ignore uncertainty, but the quantitative simulation results can help in understanding the uncertainty in the estimation of Market Value. Ultimately this could lead to investment decisions can be more accurate, efficient, and effective. Probabilitik models can better analyze the interaction between inputs representing multiple possible values, or data may not be normally distributed. The result shows the whole range of possible outcomes and the probability of achieving. With today's technology, properti assessment can easily use a Monte Carlo simulation as a tool for the quantity of existing uncertainties, many of which are used to estimate long-term investment decisions. In this model, shown step-by-step of the software is formally analyze the many risks involved with long-term investment decisions. This thesis applies two discounted cash flow model to value future cash flows related to income-producing properties: determinants models and sensitivity analysis. The success of any decision model, depends on the reliability of the underlying input. Monte Carlo simulations can lead to more optimal decisions by uncovering complex relationships associated with uncertain input. Keyword: Assessment, Discount Cash Flow, Net Present Value, Uncertainty Analysis, Market Value, Monte Carlo Simulation